Estratégias de (im) polidez no discurso de presidenciáveis 2014: a acusação como guia - Aguiar, Débora Reis (2017)
The political debate is a face-to-face verbal interaction in which the candidates interact verbally and, consequently, expose their images (faces). To protect them or to minimize threatening acts, the interlocutors usually make use of strategies of linguistic politeness. Politeness with respect to the linguistic-pragmatic studies refers to linguistic strategies used to prevent, mitigate or repair potential threats to the interlocutor or speaker’s face in order to maintain a balance in interpersonal relations. In this perspective, the objective of this study is to analyze under a linguistic-pragmatic bias these strategies as constituents of the argumentation in the corpus formed by the verbal interactions of the last electoral political debate, specifically of the first and third blocks, between the second round candidates for the presidency of the Federative Republic of Brazil, in 2014, Dilma Rousseff (PT) and Aécio Neves (PSDB), televised by Globo television network. Such selection is justified because this is a communicative interaction where actions take place that affect the relationships with himself, or with another, in which the participants emphasize the concern to maintain the balance, making use of strategies in order to protect own face, and also to avoid discomfort with their interlocutors. This analysis is based on the following questions: a) Do candidate's speeches convey polished effects? b) How are these effects structured? c) What is the relationship between politeness and political discourse? d) How politicians use strategies of politeness to carry the speech and maintain the image of themselves in the face of a debatable question? e) How to build the relationship of the political subject, and speaker, from the strategies of politeness so that he can convince his interlocutor? f) To what extent do politicians harmoniously reconcile self-preservation and respect for the others by maintaining positive projections of their images and respective groups, in accordance with the expectations of the electorate? For this proposal, the research is based on Brown and Levinson's model of politeness (1987 [1978]) and on the reformulations of this model made by Kerbrat-Orecchioni (2006). Likewise, discussions are carried out by Castilho and Castilho (1993), Castilho and Elias (2012), Santos (2012), Dias (2010), Perelman & Olbrechts-Tyteca , Fiorin (2015), Marcuschi (2004), Osakabe (1999), Charaudeau (2013), among others. From the data analysis performed, we identified politeness strategies: i) positive; ii) negative – accompanying and substitute procedures; iii) covert. In general, the results demonstrate that the politeness strategies used by the candidates of the second round of the presidential elections of 2014 tend to soften the large number of threats to the face during the debate, since it is a characteristic of the gender to attack the image of the other and to value their own image. However, presidential candidates use such strategies to preserve their image before an attentive audience (voters) in order to gain the votes and win presidential election.